Exploring interactions between Beauveria and Metarhizium strains through co-inoculation and responses of perennial ryegrass in a one-year trial - Vera, Milena; Zuern, Sarah; Henríquez-Valencia, Carlos; Loncoman, Carlos; Canales, Javier; Waller, Frank; Basoalto, Esteban; Garnica, Sigisfredo (PeerJ, 2022)
Perennial ryegrass (Lolium perenne L.) possesses a high level of nutritional quality and is widely used as a forage species to establish permanent pastures in southern Chile. However, the productivity of most such pastures is limited by various environmental agents, such as insect pests and drought. In this context, our work stresses the need for elucidating the ability of fungal endophytes to establish interactions with plants, and to understand how these processes contribute to plant performance and fitness. Therefore, we evaluated the colonization and impact of two native strains of the endophytic insect-pathogenic fungus (EIPF) group isolated from permanent ryegrass pastures in southern Chile. Roots and seeds of ryegrass and scarabaeid larvae were collected from nine different ryegrass pastures in the Los Ríos region of southern Chile to specifically isolate EIPFs belonging to the genera Beauveria and Metarhizium. Fungal isolations were made on 2% water agar with antibiotics, and strains were identified by analyzing the entire internal transcribed spacer (ITS) 1-5.8S-ITS2 ribosomal DNA region. Four strains of Beauveria and 33 strains of Metarhizium were isolated only in scarabaeid larvae from ryegrass pastures across four sites. Experimental mini-pastures that were either not inoculated (control) or co-inoculated with conidia of the strains Beauveria vermiconia NRRL B-67993 (P55_1) and Metarhizium aff. lepidiotae NRRL B-67994 (M25_2) under two soil humidity levels were used. Ryegrass plants were randomly collected from the mini-pastures to characterize EIPF colonization in the roots by real-time PCR and fluorescence microscopy. Aboveground biomass was measured to analyze the putative impact of colonization on the mini-pastures’ aboveground phenotypic traits with R software using a linear mixed-effects model and the ANOVA statistical test. Seasonal variation in the relative abundance of EIPFs was observed, which was similar between both strains from autumn to spring, but different in summer. In summer, the relative abundance of both EIPFs decreased under normal moisture conditions, but it did not differ significantly under water stress. The aboveground biomass of ryegrass also increased from autumn to spring and decreased in summer in both the inoculated and control mini-pastures. Although differences were observed between moisture levels, they were not significant between the control and inoculated mini-pastures, except in July (fresh weight and leaf area) and October (dry weight). Our findings indicate that native strains of B. vermiconia NRRL B-67993 (P55_1) and M. aff. lepidiotae NRRL B-67994 (M25_2) colonize and co-exist in the roots of ryegrass, and these had little or no effect on the mini-pastures’ aboveground biomass; however, they could have other functions, such as protection against root herbivory by insect pests.
Keywords: Beauveria; Co-inoculation; Root colonization; Water stress; Metarhizium; Fungal endophytes; Entomophatogenic fungi; qPCR Miner; Fluorescence microscopy; Perennial ryegrass